2006
DOI: 10.1542/peds.2006-0198
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Immunogenicity in 6- to 23-Month-Old Children: Are Identical Antigens Necessary for Priming?

Abstract: Although the immune response to the identical A/H1N1 vaccine antigen was similar in both groups, priming with different A/H3N2 antigens and B antigens in the spring produced a lower immune response to both antigens than that shown in children who received 2 doses of the same vaccine in the fall. However, approximately 70% of children in the spring group had a protective response to the H3N2 antigen after 2 doses. Initiating influenza immunization in the spring was superior to 1 dose of trivalent inactivated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 19 publications
1
49
1
2
Order By: Relevance
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
“…Classification of fever varied across studies, but a majority of studies [22,25,27,[29][30][31]34,35,37,38] provided data on fever ≥ 38 °C. We used these studies for meta-analysis of fever rate and one additional study [39], where we assumed a fever definition of ≥ 38 °C based on two similar studies by the same lead author [31,35].…”
Section: Characteristics Of Randomised Controlled Trialsmentioning
confidence: 99%
See 3 more Smart Citations